Practical endocrinology and diabetes in children - Raine, Joseph E. (Wiley-Blackwell, 2011)
"This practical, highly clinical, concise, and up-to-date account of pediatric endocrinology and diabetes serves as a concise and convenient companion to more extensive textbooks. The third edition contains a variety of new features such as key web links, key guidelines and courses for endocrinologists and pediatricans, and five case studies per chapter illustrating diagnostic difficulties. Chapters include sections on how to deal with emergencies, potential pitfalls, guidelines on which conditions should be discussed with a specialist, controversial areas, and future developments"--Provided by publisher